2023
DOI: 10.3390/antiox12081553
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and Glutaredoxin—Key Players in Cellular Redox Homeostasis and Signaling

Abstract: This Special Issue of Antioxidants on Glutathione (GSH) and Glutaredoxin (Grx) was designed to collect review articles and original research studies focused on advancing the current understanding of the roles of the GSH/Grx system in cellular homeostasis and disease processes. The tripeptide glutathione (GSH) is the most abundant non-enzymatic antioxidant/nucleophilic molecule in cells. In addition to various metabolic reactions involving GSH and its oxidized counterpart GSSG, oxidative post-translational modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…As a dimeric disulfide oxidoreductase, GR can catalyze the reduction of GSH disulfide (GSSG) to GSH for resisting oxidative stress. This process helps maintain the redox environment in human and animal cells ( 66 ). Consistent with previous findings in various fish species ( 46 ), our study demonstrates higher GR activities and GSH levels in fish fed with adequate SePCH, indicating that sufficient SePCH can enhance cellular redox homeostasis and increase antioxidant capacities by boosting GSH synthesis in the liver and intestine of largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…As a dimeric disulfide oxidoreductase, GR can catalyze the reduction of GSH disulfide (GSSG) to GSH for resisting oxidative stress. This process helps maintain the redox environment in human and animal cells ( 66 ). Consistent with previous findings in various fish species ( 46 ), our study demonstrates higher GR activities and GSH levels in fish fed with adequate SePCH, indicating that sufficient SePCH can enhance cellular redox homeostasis and increase antioxidant capacities by boosting GSH synthesis in the liver and intestine of largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study found significant influence of key genes involved in glutathione metabolism, attributed to the inactivation of AaBemA, AaNoxB, AaTrr1, AaGlr1, AaYap1, and A. alternata wildtype under ROS stress. Glutathione, an important metabolite in eukaryotes, plays a key role in protecting cells from oxidative damage through direct scavenging of various oxidants [59,60]. We also found that significant impacts of inactivation of AaBemA, AaNoxB, AaTrr1, and AaGlr1 on the expression of genes enriched in various crucial molecular functions and pathways such as oxidoreductase activity, transmembrane transporter activity, and multiple metabolic pathways related to the regulation of ROS tolerance, providing insights into ROS detoxification and NADPH oxidase-mediated responses.…”
Section: Discussionmentioning
confidence: 65%
“…GSH, a ubiquitous cellular thiol compound involved in ROS scavenging and antioxidant defense against electrophiles, serves as a key regulator of redox status within cells. Since GSH is oxidized to GSSG when reacting with ROS or electrophiles, the GSH/GSSG ratio reflects the oxidation state, and a decrease in this ratio is related to the accumulation of excessive ROS ( Hanko et al ., 2019 ; Chai and Mieyal, 2023 ). It stands to reason therefore that increasing GSH levels may be an effective strategy to protect cells from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%